Upaya Deteksi Dini Faktor Risiko Penyakit Tidak Menular pada Lansia melalui Pemeriksaan Kesehatan Dasar di Posyandu Palur, Karanganyar - Liss Dyah Dewi Arini; Anggraini Sih Prabandari (Lembaga Pengembangan Kinerja Dosen, 2026)
Non-communicable diseases (NCDs) such as high blood pressure, diabetes, high cholesterol, and gout are increasingly common health problems in the community. Lack of public awareness of the importance of regular health checks means many cases of NCDs go undetected in their early stages. This initiative aims to detect risk factors for NCDs early by conducting basic health checks in the community. The methods used include anthropometric measurements and simple health checks, such as weight, height, blood pressure, blood sugar, uric acid levels, cholesterol levels, waist circumference, and hip circumference. The results showed that some people still had test results above normal limits. These include blood sugar levels greater than or equal to 200 mg/dL, blood pressure greater than or equal to 140/90 mmHg, high uric acid levels greater than or equal to 7 mg/dL in men and 6 mg/dL in women, and cholesterol levels greater than or equal to 200 mg/dL. These findings indicate the existence of risk factors for non-communicable diseases (NCDs) that require attention and follow-up through health education and routine check-ups. These early detection activities help raise public awareness of the importance of regular health check-ups as a way to prevent and control NCDs early.